Dynamic Chronological Changes in Serum Triglycerides Are Associated With the Time Point for Non-alcoholic Fatty Liver Disease Development in the Nationwide Korean Population Cohort - Rim, John Hoon; Youk, Taemi; Gee, Heon Yung; Cho, Jooyoung; Yoo, Jongha (Frontiers in Medicine, 2021)
Background: We investigated the effects of anthropometric, laboratory, and lifestyle factors on the development of nonalcoholic fatty liver disease (NAFLD) in a nationwide, population-based, 4-year retrospective cohort. Methods: The propensity score-matched study and control groups contained 1,474 subjects who had data in the Korean National Health Insurance Service-National Sample Cohort in 2009, 2011, and 2013. NAFLD was defined using medical records of a diagnosis confirmed by primary clinicians and meeting two previously validated fatty liver prediction models. Chronological changes in anthropometric variables, laboratory results, and lifestyle factors during two periods were compared between patient and control groups in order to find out parameters with consistent dynamics in pre-NAFLD stage which was defined as period just before the NAFLD development. Results: Among the 5 anthropometric, 10 laboratory, and 3 lifestyle factors, prominent chronological decremental changes in serum triglycerides were consistently observed during the pre-NAFLD stage, although the degrees of changes were more predominant in men than women. Furthermore, weight and waist circumference changes during the pre-NAFLD stage were noticeable only in women, which suggest gender difference in NAFLD. Conclusion: Early screening strategies for people with abrupt chronological changes in serum triglycerides to predict NAFLD development before the progression is recommended.